Rationale and design of mDOT-HuA study: a randomized trial to assess the effect of mobile-directly observed therapy on adherence to hydroxyurea in adults with sickle cell anemia in Tanzania. Issue 1 (December 2016) - Makubi, Abel; Sasi, Philip; Ngaeje, Mariam; Novelli, Enrico; Mmbando, Bruno; Gladwin, Mark; Makani, Julie
Abstract Background Hydroxyurea (HU) has been demonstrated to be efficacious in reducing complications in individuals with sickle cell anemia (SCA) but poor adherence is a barrier. Directly Observed Therapy (DOT) has been shown to improve adherence in various chronic diseases but there is limited data in adults with SCA. Methods and design To examine the effect of mobile-directly observed therapy (mDOT) on adherence to HU (mDOT-HuA) in adults with SCA at Muhimbili National Hospital in Tanzania. The mDOT-HuA study is a single centre, prospective, randomized, open label clinical trial. One-hundred individuals with SCA with haemoglobin SS genotype, aged ≥18 years, living in Dar es Salaam, able and willing to record and submit videos electronically will be included. Participants will be divided into two treatment arms; 50 in the standard monitoring (SM) arm will receive mobile phones and fixed dose HU therapy with standard monitoring; 50 in the mDOT arm will receive mobile phones, fixed dose HU therapy with standard monitoring and a mobile directly observed web based medication adherence monitoring system. The primary outcome is the proportion of participants achieving ≥80 % HU adherence compared between the two arms as assessed through medication possession ratio at the end of 3 months of treatment. REDCap, an open source software application will be used to collect data using clinical research forms. The proportions of adherence in the two arms will be compared by Fisher's exact test. Analysis of outcomes will have performed by both the intention-to treat and per-protocol methods. Discussion Should this study become sucessful, it will have the potential for the development of novel strategies for improving HU adherence in SCA. Trial registration ClinicalTrials.gov Identifier:NCT02844673, registered on 25th t July 2016 (retrospectively registered).